HOXA10 is Overexpressed in Human Ovarian Clear Cell Adenocarcinoma and Correlates With Poor Survival. Issue 8 (1st November 2009) - Li, Bin; Jin, Hongyan; Yu, Yinhua; Gu, Chao; Zhou, Xianrong; Zhao, Naiqing; Feng, Youji
Abstract : Human homeobox gene (HOX) A10 is a homeobox allotype gene of the HOXA family in the HOX family. Human homeobox gene A10 may play an important role in cancer development. However, the role of HOXA10 in the carcinogenesis of ovarian clear cell adenocarcinoma (OCCA) has not been established. We have evaluated the prognostic significance of HOXA10 expression for human OCCA and the effects of HOXA10 on proliferation, motility, and invasion of OCCA cells. We found that HOXA10 was not expressed in normal ovarian epithelium, ovarian endometrial cysts, and ovarian serous carcinomas, but 20 (68.9%) of the 29 OCCAs were positive for the expression of HOXA10. Human homeobox gene A10 expression was negatively correlated to the 5-year survival of OCCA patients ( R = −0.442, P = 0.043). When a HOXA10 expression vector was stably transfected into a human OCCA cell line, ES-2, the proliferation rate of ES-2-HOXA10 was much higher than the vector control, the motility of ES-2-HOXA10 cells was significantly increased compared with the control ( P < 0.05), and the invasion of ES-2-HOXA10 cells was also much higher than the vector control ( P < 0.01 at 5 hours and 12 hours after scratching). In conclusion, HOXA10 was overexpressed in OCCA and was correlated with poor survival. HOXA10 promotes proliferation, migration, and invasion of OCCA cells. Human homeobox gene A10 could be a promising prognostic marker for OCCA.